Biofeedback eletromiográfico como suporte ao exercício de acoplamento de língua em mulheres: ensaio clínico randomizado - Corrêa, Mariana da Silva (2024)
The use of Electromyographic Biofeedback is promising due to its ability to enable patients to learn and monitor new muscle patterns through visual reinforcement. This study aims to evaluate the myoelectric activity of the suprahyoid region pre and post-tongue coupling intervention immediately with and without Electromyographic Biofeedback and the self-perception of this technique in healthy women. This is a randomized, double-blind, parallel, and placebo-controlled clinical trial. For the data collection itself, electromyographic evaluation of the suprahyoid region was performed during rest, maximal voluntary contraction, and liquid swallowing, both pre and post-intervention. The intervention was conducted through block randomization, where participants were distributed into three distinct groups. The training proposals differed in whether they did or didn't involve Electromyographic Biofeedback, but regardless of the group, participants performed the same tongue coupling exercise in three sets of 15 seconds, with ten seconds of rest between each of them, and 30 seconds of rest between one set and another. Group 1 performed the training while visualizing the graph generated via Electromyographic Biofeedback mode, Group 2 visualized the equipment screen in its evaluation mode, and Group 3 only performed the exercise. After the intervention, participants from Groups 1 and 2 completed a self-perception questionnaire regarding the technique used in the study. As a result, 230 women were evaluated, of whom 57 were analyzed, with 19 volunteers in each group. The data has already been tabulated and statistically analyzed using Wilcoxon, Kruskal-Wallis, and Chi-square tests, considering a significance level of 5%. Overall, no significant change was identified regarding the myoelectric activity of the suprahyoid region following the different intervention proposals. However, regarding self-perception results, a significant association was noted both in the influence of Biofeedback during exercise performance and in the support provided by the technique in its execution. These results highlight the importance of evaluating both quantitative aspects and patients' perception when analyzing proposed interventions.